2008
DOI: 10.1103/physrevlett.100.145902
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Hall Effect for the Phonon Heat Conductivity in Paramagnetic Dielectrics

Abstract: The theory of anomalous Hall effect for the heat transfer in a paramagnetic dielectric, discovered experimentally in [1], is developed. The appearance of the phonon heat flux normal to both the temperature gradient and the magnetic field is connected with the interaction of magnetic ions with the crystal field oscillations. In crystals with an arbitrary phonon spectrum this interaction creates the elliptical polarization of phonons. The kinetics related to phonon scattering induced by the spin-phonon interacti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
85
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 10 publications
1
85
0
Order By: Relevance
“…An accurate evaluation of the integrals in Eq. (13) confirms that the primary contribution to κ xx comes from ω ≈ T = 5K. On the other hand the dominant contribution to κ xy comes from ω ∼ 30K -the phonon Hall effect is due to relatively "hot" phonons.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…An accurate evaluation of the integrals in Eq. (13) confirms that the primary contribution to κ xx comes from ω ≈ T = 5K. On the other hand the dominant contribution to κ xy comes from ω ∼ 30K -the phonon Hall effect is due to relatively "hot" phonons.…”
supporting
confidence: 54%
“…We stress that the PHE in TGG relies specifically upon scattering from superstoichiometric Tb 3+ ions, not just scattering from any impurities. This observation was not considered in all previous suggestions 12,13,15 for the mechanism behind the PHE. In this Letter, motivated by the above observation, we show that the PHE originates from the resonant skew scattering of phonons from the crystal field states of superstoichiometric Tb 3+ ions.…”
mentioning
confidence: 88%
“…Recently there has been surging experimental interest in studying the thermal Hall effect in various systems, such as the phonon Hall effect [2,3], magnon Hall effect [4], and so on. There are also many theoretical efforts to study these phenomena [5][6][7][8]. However, most of these theoretical studies face a fundamental issue: direct application of the Kubo formula, when done correctly without questionable ''tricks'' [9], always yields unphysical divergence at zero temperature [10,11].…”
mentioning
confidence: 99%
“…Strohm et al observed the thermal Hall effect of phonons in a paramagnetic insulator of terbium gallium garnet [72]. The result was explained by the interaction of local magnetic ions with the local orbital angular momentum of oscillating surrounding ions [73,74]. The thermal Hall effect of magnons was also observed in an insulating ferromagnet LU 2 V 2 O 7 with pyrochlore structure [75], and the result was explained in terms of a Dzyaloshinskii-Moriya interaction.…”
Section: Thermal Hall Effect Of Phonons and Magnonsmentioning
confidence: 81%